The Effect of Scaffolding-Based Worksheet in the Discovery Learning Model on Physics Learning Outcomes - Elven Hardyus Samadaya Nehe; Gusnedi Gusnedi; Hufri Hufri; Silvi Yulia Sari (Physics Learning and Education, 2023)
Physics learning outcomes are underdeveloped because the learning model is still teacher-centered and needs to involve by teaching materials that enhance the learning process.  The discovery learning model, is one of learning model that can enhance physics learning outcomes, which involves engaged and student-centered. Media and teaching materials must support the applied discovery learning model by using the worksheets with scaffolding are effective and practical for the discovery learning model. This study aims to see whether there is an effect of the application of scaffolding-based worksheet in the discovery learning model on the physics learning outcomes of students. The type of research conducted was a quasi-experiment using the Randomized Posttest Only Control Group Design. The population of this study were all students of class XI.F of Senior High School in Padang. Sampling was done with Purposive Sampling technique. Data analysis techniques used are normality test, homogeneity test and hypothesis test. According to data analysis with hypothesis testing obtained th<tt where 2.129<1.667 H0 is rejected and H1 is accepted, it can be concluded in the study that application of scaffolding-based worksheet in the discovery learning model has a significant effect on the physics learning outcomes on the knowledge aspect. The results of this study are used as input for teachers and prospective teachers. Improve themselves in connection with the teaching that has been done and the student learning outcomes that have been achieved by varying the learning model with the appropriate learning media to improve student physics learning outcomes.